2019
DOI: 10.32707/ercivet.648575
|View full text |Cite
|
Sign up to set email alerts
|

Hasmer Koyunu Mandibula’sı Üzerinde Makroanatomik ve Morfometrik İncelemeler

Abstract: Atıf yapmak için: Özüdoğru Z, İlgün R, Özdemir D. Hasmer koyunu mandibula'sı üzerinde makroanatomik ve morfometrik incelemeler. Erciyes Üniv Vet Fak Derg 2019; 16(3): 218-223.Özet: Çalışma Hasmer koyunu mandibula'sı üzerinde bazı morfometrik değerleri ortaya koymak amacıyla yapılmıştır. Çalışmada Bahri Dağdaş Tarımsal Araştırma Enstitüsü'nden temin edilen reforme erişkin 8 adet Hasmer koyunu mandibula'sı kullanıldı. Hasmer koyununun mandibula'sı 19 noktadan ölçülmüş ve elde edilen değerler diğer koyun ırklarıy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…In the literature, with respect to the mandibular length and height were 167. 8 23 . This parameter was determined as 128.87 mm in female Abaza goats and 118.84 mm in male Abaza goats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature, with respect to the mandibular length and height were 167. 8 23 . This parameter was determined as 128.87 mm in female Abaza goats and 118.84 mm in male Abaza goats.…”
Section: Discussionmentioning
confidence: 99%
“…and 94.2 mm in Hemshin sheep18 , 152.4 and 87.0 mm in Morkaraman sheep,19 and Tuj sheep 147.8 and 85.4 mm19 , respectively. 157.6 and 95.7 mm in Mehra-ban sheep,20 181.6 and 107.9 mm in Barbados sheep,21 in Yankasa sheep,22 198.0±0.28 and 129.0±0.57 were reported as 186.30±9.30 and 108.68±2.36 mm in Hasmer sheep,23 in Awassi sheep 26 mandibular length 180.22±11.91 while Avdic et al24 ., reported that it was 176.0 and 99.6 mm in a study on sheep in Sarajevo. In Abaza goats 158,73 mm and 90,46 mm in females 148,72 and 88,60 mm in males respectively.…”
mentioning
confidence: 91%
See 3 more Smart Citations